Predicting Success of Deformity Correction With Tension Band Plating in Early-Onset Tibia Vara. Issue 5 (24th May 2023) - Walker, Janet L.; Dueber, David M.; Stephenson, Lindsay P.; Scott, Allison C.; Lerman, Joel A.; Powell, Kenneth P.; Ackman, Jeffery D.; Westberry, David E.; Nossov, Sarah B.; Franklin, Corinna C.
Abstract : Background: Angular deformity correction with tension band plating has not been as successful in early-onset tibia vara (EOTV) as it has been in other conditions. Our hypothesis is that perioperative factors can predict the success of lateral tibial tension band plating (LTTBP) in patients with EOTV. Methods: A retrospective review was performed at 7 centers evaluating radiographic outcomes of LTTBP in patients with EOTV (onset <7 y of age). Single-event tibial LTTBP outcome was assessed through medial proximal tibial angle (MPTA). The final limb alignment following comprehensive limb growth modulation (CLGM), which could include multiple procedures, was assessed by mechanical axis zone (MAZone), mechanical tibio-femoral angle (mTFA), and mechanical axis deviation (MAD). Preoperative age, weight, deformity severity, medial physeal slope, and Langenskiöld classification +/- modification were investigated as predictors of outcome. Success was defined as the correction or overcorrection to normal age-adjusted alignment. The minimum follow-up was 2 years except when deformity correction, skeletal maturity, or additional surgery occurred. Results: Fifty-two patients with 80 limbs underwent 115 tibial LTTBP procedures at a mean age of 5.3 y, including 78 primary, 21 implant revisions, and 15 reimplantations for recurrence. Tibial LTTBP resulted in a mean change of +8.6 o in MPTA and corrected 53% of tibias. CLGM resulted in MAD correction for 54% of limbs. Univariate analysis showed that success was best predicted by preoperative age, weight, MPTA, and MAD. Multivariate analysis identified that preoperative-MPTA/MAD and preoperative-weight<70 kg were predictive of MPTA and MAD correction, respectively. The probability of success tables are presented for reference. Conclusion: Successful correction of MPTA to age-adjusted norms following a single-event LTTBP occurred in 53% of tibias and was best predicted by preoperative-MPTA and preoperative body weight <70 kg. Comprehensive growth modulation corrected limbs in 54%. The probability of correction to age-adjusted MAD is best estimated by preoperative-MAZone 1 or 2 (MAD ≤40 mm). Limbs with preoperative-MAD>80 mm improved, but ultimately all failed to correct completely with CLGM. Osteotomy may need to be considered with these severe deformities. While modified Langenskiöld classification and medial physeal slope have been shown to predict the outcome of osteotomy, they were not predictive for LTTBP. Change in MPTA was common after physeal untethering. Level of Evidence: Level—III.